El reciclaje vivencial como propuesta para el tratamiento de residuos sólidos generados en la I.E Juan Velasco Alvarado - Coral Vásquez, Roberto Carlos (2015)
The present investigaton had as objective to determine the contribuiton of experiential Recycling in the treatment of the solid waste generated in the Educational lnstitution "Juan Velasco Alvarado", located in Bellavista province, San Martín Region. In this sense it launched three fundamental tasks such as the characterization of the solid waste generated in the institution, the development of workshops to strengthen the cognitive part ofthe pupiis and the actions reiated to the development of favorable attitudes. In regard to the experiential recycling, we worked in the manufacture omaments throuah the recvclina of oaoer and cardboard, plastic bottles and tetra oack. lt also worked under the assumption that if students are educated with experiential workshops of recycling then your contribution will be significant for the treatment of sol id waste, which constituted the research hypothesis, the same that was contrasted by the Student test for paired difference, with 95% confidence. in the operative parí, i worked with a sampie of ·14 students of the first grade and 13 students in the se.cond grade of secondary s.choo.!, making .a total of 27 students who were instructed in workshops and evaluated before and after this process through a questionnaire that consisted of 14 items. On the other hand, the type of research applications and conducted under the quasi-experimental design, had as main source for obtaining data to students and teachers who strongly supported sin ce it was an institutional problem. Among the conclusions we can affirm that the experiential recycling has contributed significantly to improve the treatment of the solid waste generated in "Juan Velasco Alvarado" Educational lnstitution from Bellavista. In addition, students improved their attitudes with respect to the ca re and conservation of the environment through recycling, which was evidenced by the massive participation in the workshops, which allowed them to also significant achievements in the cognitive part.